Intravitreal Polymeric Nanocarriers with Long Ocular Retention and Targeted Delivery to the Retina and Optic Nerve Head Region - Vijayabhaskarreddy Junnuthula; Amir Sadeghi Boroujeni; Shoupeng Cao; Shirin Tavakoli; Roxane Ridolfo; Elisa Toropainen; Marika Ruponen; Jan C. M. van Hest; Arto Urtti (MDPI AG, 2021)
Posterior eye tissues, such as retina, are affected in many serious eye diseases, but drug delivery to these targets is challenging due to various anatomical eye barriers. Intravitreal injections are widely used, but the intervals between invasive injections should be prolonged. We synthesized and characterized (1H NMR, gel permeation chromatography) block copolymers of poly(ethylene glycol), poly(caprolactone), and trimethylene carbonate. These polymers self-assembled to polymersomes and polymeric micelles. The mean diameters of polymersomes and polymeric micelles, about 100 nm and 30-50 nm, respectively, were obtained with dynamic light scattering. Based on single particle tracking and asymmetric flow field-flow fractionation, the polymeric micelles and polymersomes were stable and diffusible in the vitreous. The materials did not show cellular toxicity in cultured human umbilical vein endothelial cells in the Alamar Blue Assay. Pharmacokinetics of the intravitreal nanocarriers in the rabbits were evaluated using in vivo fluorophotometry. The half-lives of the polymersomes (100 nm) and the micelles (30 nm) were 11.4-32.7 days and 4.3-9.5 days. The intravitreal clearance values were 1.7-8.7 µL/h and 3.6-5.4 µL/h for polymersomes and polymeric micelles, respectively. Apparent volumes of distribution of the particles in the rabbit vitreous were 0.6-1.3 mL for polymeric micelles and 1.9-3.4 mL for polymersomes. Polymersomes were found in the vitreous for at least 92 days post-dosing. Furthermore, fundus imaging revealed that the polymersomes accumulated near the optic nerve and retained there even at 111 days post-injection. Polymersomes represent a promising technology for controlled and site-specific drug delivery in the posterior eye segment.